Answer:
f(g(3)) = 3
Step-by-step explanation:
We are told to solve for f(g(3)). This is also saying f of g of 3.
To find f(g(3)), we need to plug 3 in for x in g(x), since it says g(3).
g(x) = 3(3) - 4
Solve.
= 9 - 4
g(x) = 5
Now, we plug that into f(x), because g(x) was placed inside f and replaces the x variable of f(x).
f(5) = 2(5) - 7
Solve.
= 10 - 7
f(5) = 3.
f(g(3)) = 3
#teamtrees #WAP (Water And Plant)
Answer:
4x-7y = -21
Step-by-step explanation:
1. Move 4/7x to the other side
-4/7x+y=-3
2. Multiply both sides by -7
4x-7y=-21
Answer:
7
Step-by-step explanation:
you need to use PEMDAS
3 x 3 x 3 = 27 divided by 9 is 3 and 10-3=7
Alright, let's do all of these (though this is a bit long).
1.
The constant is 1.8. All other values are coefficients to variables, which as the name implies will change.
2.
1 hour is 60 minutes, 1 minute is 60 seconds.
So, 4.2 *60 *60 = 15120 seconds.
3.
<span>−5x−4(x−6)=−3-5x-4(x-6)=-3
Let's move all x to one side, and all other numbers to another.
-5x-4(x-6)=-3-5x-4(x-6)=-3
x can be any value you want, if you actually solve this you'll only end up with -3 = -3, which is correct, of course.
Let me show you:
</span><span>−5x−4(x−6)=−3-5x-4(x-6)=-3
+5x +4(x-6) +5x +4(x-6)
-3 = -3
The value of x is irrelevant, then. X can be any real number.
4.
I'm going to assume it was an error in printing with this? If not please correct me.
m=a+2b(or b2)
subtract 2b from each
a=m-2b
(This question seems kind of odd. We should probably address this in the comments.)
5.
</span><span>5(x−2)<−3x+6
Move all x to one side, numbers to other.
5x-10<-3x+6
+3x +3x
+10 +10
8x<16
/8
<span>x < 2
</span>6.
y-3=3(x-5)
alright, to find zeros set one variable to zero and solve
x first
-3=3x-15
+15 +15
3x=12
/3
x=4
x-int is (4,0)
now y
</span>y-3=3(0-5)
y-3=-15
+3 +3
y=-12
so y-int is (0,-12)
i've got to sleep now so i'll do the rest tomorrow. Sorry for the incomplete answer.
823.582% increase between the initial price and the current price.